Portfolios of Political Ties and Business Group Strategy in Emerging Economies - Zhu, Hongjin; Chung, Chi-Nien (Administrative Science Quarterly, 2014)
Using data on 290 business groups, this study examines how ties with rival political parties maintained by Taiwanese firms from 1998 through 2006 affected business strategies, specifically the unrelated diversification into new industries. Taiwan’s recent democratization and emerging economy provide an ideal setting for studying the economic impact of firms’ ties with rival political parties. By focusing on a firm’s entire portfolio of ties instead of strictly dyadic business–government ties, we offer a novel model that demonstrates how the interplay of various ties affects a firm’s strategy differently under different forms of government. Our analysis shows that under a united government, ties to the ruling party facilitate entries of business groups into unrelated industries, while ties to the opposition parties inhibit such moves. Portfolios of ties to both the ruling and opposition parties impose additional obstacles to market entry. Under a divided government, however, ties to the ruling party are conducive to market entry, and portfolios of ties to both the ruling party and the opposition party with legislative authority offer a further boost. Regardless of type of government, the effect of having a portfolio of political ties tends to be mitigated by a firm’s internal resources and capabilities: a firm with sufficient resources and market entry experience has a better chance of achieving its goals even when a dominant political party withholds its support. Our study highlights the tradeoffs that politically connected firms confront in emerging economies with underdeveloped political and market institutions.